Visions of Greece [videorecording (DVD)] - Toperoff, Sam; Tal, Duby, 1955- (Distributed by Acorn Media, 2004)
Includes two programs: Visions of Greece, which covers the most famous cities and sites, and Visions of Greece: Off the beaten path, which features rarely visited locales. Also includes nearly an hour of bonus footage not seen on PBS.